Analysis of the insertion of priority family farmers in public calls for school food (Research, Society and Development, 2021)
Introduction: Law nº 11.947/2009 required the application of at least 30% of the funds transferred by the federal government, in the purchase of food from Family Agriculture (AF) for school meals, originating, preferably, from the local level, prioritizing the vulnerable communities, with organic and agroecological genera and groups of suppliers with formal participation. Objective: the present study carried out a historical series of Public Calls (PC), observing the occurrence of the acquisition of foodstuffs according to the prioritization criteria established in the PNAE legislation in the municipality of São Cristóvão/SE. Methodology: This is a case study, with documentary analysis. PC and sales contracts related to the acquisition of AF products in the period from 2010 to 2020 were analyzed. Results: Contrary to the Law, it was evident that throughout the decade of study, family farmers living in the municipality had less participation in the PC than the others outside the local territory. There was less participation of vulnerable communities in the program and the lack of access for producers of organic and agroecological products. In accordance with the legislation, there was a greater participation of formal groups of farmers in all PC processes. Conclusion: Intersectoral actions are necessary to facilitate access and ensure the participation of these groups in PCs, so that the program, as a public policy, guarantees food and nutrition security for schoolchildren and local communities.